2014
DOI: 10.4103/1658-354x.140903
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of complex regional pain syndrome type 1 using single injection interscalene brachial plexus block

Abstract: Complex regional pain syndrome (CRPS) type 1 of the upper limb is a painful and debilitating condition. Interscalene brachial plexus block (ISB) in conjugation with other modalities was shown to be a feasible therapy with variable success. We reported a case of CRPS type 1 as diagnosed by International Association for the Study of Pain criteria in which pharmacological approaches failed to achieve adequate pain relief and even were associated with progressive dysfunction of the upper extremity. Single injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Brachial plexus block is used for regional anesthesia during upper extremity surgery (arm, elbow, forearm, wrist, and hand) [ 35 ]. In chronic pain management, ultrasound-guided hydrodissection of the brachial plexus has been used to treat severe neck sprains (brachial plexus injury without rupture; it is only used to treat neuropraxia with or without axonotmesis) with radiating pain to the ipsilateral upper limb [ 36 ], CRPS [ 37 ] involving the ipsilateral upper limb, and thoracic outlet syndrome or other double/triple crush syndromes involving the ipsilateral upper limb [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Brachial plexus block is used for regional anesthesia during upper extremity surgery (arm, elbow, forearm, wrist, and hand) [ 35 ]. In chronic pain management, ultrasound-guided hydrodissection of the brachial plexus has been used to treat severe neck sprains (brachial plexus injury without rupture; it is only used to treat neuropraxia with or without axonotmesis) with radiating pain to the ipsilateral upper limb [ 36 ], CRPS [ 37 ] involving the ipsilateral upper limb, and thoracic outlet syndrome or other double/triple crush syndromes involving the ipsilateral upper limb [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Medical treatments can also classify the pain: stellate ganglion blocks will only relieve CRPS [6, 100,101]. Other therapies for CRPS include botulinum toxin, which can be used to treat muscular trigger points [102] when found, and electroacupuncture, which has been found effective in controlling experimental brachial plexus pain in rats [103]. We have not found any publication reporting the use of electroacupuncture in human beings.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…CRPS is the exception as further surgery outside trapped nerve decompression seems to have a negative impact on the outcome [101]. In these cases either an interscalene [102] or stellate ganglion block [110] or a cervical spinal cord stimulator [111][112][113] is recommended instead. The phantom limb pain only improves with central nervous system procedures [114,115].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A sonographically assisted interscalene brachial plexus block (single injection of 30 ml, 0.25 % bupivacaine) resulted in immediate pain relief and gradual functional recovery. At 3-months follow-up the patient showed complete pain relief and normal limb function [7]. Wang et al (2001) reported the case of a 32-year-old man suffering from acute CRPS in his right upper limb following carpal tunnel release.…”
Section: Discussionmentioning
confidence: 97%